STANDAR ISI SEBAGAI ACUAN PENGEMBANGAN MUTU KURIKULUM PENDIDIKAN AGAMA ISLAM - Isnawati Nur Afifah Latif (Al Hikmah: Jurnal Studi Keislaman, 2021)
Abstract. Each unit of Islamic education is required to be able to develop acurriculum by orienting on increasing faith and piety as a guide in digging scienceand technology and to dig and to deceive the cultural diversity and potential of theregion, so that a skilled and virtuous figure will appear in order to meet worlddemands. work. In an effort to fulfill the objectives of the vision and mission ofnational education, the government authorizes the implementers of formal educationprograms to conduct quality assurance in each education program. The curriculum ofIslamic religious education includes efforts to realize harmony, compatibility,conformity, and balance between human relationship with Allah, human relationshipwith humans, human relationship with other creatures and the environment, humanrelationship with himself. The main aspect that should be considered in thepreparation of Islamic education curriculum materials is the change of cognitive,psychomotor, and affective aspects of students for the better. Efforts to make theIslamic religious education curriculum effective can be done by implementing thecurriculum in accordance with the principles and principles of the curriculum.Keywords: Content Standards 1, Curriculum Quality 2, Islamic education 3